Paracoccidioidomycosis in patients with Lymphoma and review of published literature - Ruiz e Resende, Lucilene Silva [UNESP]; Yasuda, Alice Gadotti [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Marques, Silvio Alencar [UNESP]; Niero-Melo, Ligia [UNESP]; Defaveri, Julio [UNESP]; Custodio Domingues, Maria Aparecida [UNESP] (Springer, 2015)
This paper describes four new cases of lymphomas, two Hodgkin lymphomas and two non-Hodgkin lymphomas in patients with paracoccidioidomycosis. All had mycosis diagnosed before lymphomas with Paracoccidioides brasiliensis demonstrated in several lymph nodes, as seen in the disseminated form of the disease. When lymphoma was diagnosed, one patient was under regular paracoccidioidomycosis treatment and in clinic-serological remission for this disease, another was under regular treatment but with clinic-serological mycosis activity, one had abandoned paracoccidioidomycosis treatment 6 years earlier, and the other had not yet received any kind of antifungal drugs. Three patients received treatment for lymphomas with one remaining in remission until now, one achieving tumor remission which relapsed years later, and one having only residual lymphoma in bone marrow for a decade but clinically well. All three experienced paracoccidioidomycosis clinical remission, however, serology became negative just in one. Similar previously described cases were reviewed: five Hodgkin lymphomas, three non-Hodgkin lymphomas, and one described only as "lymphoma" without specifying type; a summary of their findings is presented. Finally, there is also a brief discussion on the possible pathophysiological mechanisms involved in the concomitance of these two disorders.
Keywords: Lymphoma; Cancer; Neoplasia; Paracoccidioidomycosis; Paracoccidioides brasiliensis